ACADEMIC PERSONNEL MANAGEMENT AT CLASSICAL UNIVERSITY - Yuriy A. Bubnov (Moscow Polytechnic University, 2016)
The article focuses on the problem of academic staff management at classical university. The causes of the negative trends in the staffing of universities are explored and ways to overcome them are also suggested. The use of empirical data allows the author to trace the influence of innovative activity on decrease in the outflow of young scholars and professors and on the rejuvenation of the teaching staff. Using the specific university as an example, the author considers the implementation process of such innovative form of human resources strategy as a creative approach to decision-making on staffing issues.